In vitro effects of selective serotonin reuptake inhibitors on Cryptococcus gattii capsule and biofilm - Viveiro, Letícia Rampazzo Da Gama [UNESP] (2024)
Infections caused by Cryptococcus gattii mainly affect immunocompetent individuals and the treatment presents important limitations. This study aimed to validate the efficacy of selective serotonin reuptake inhibitors (SSRI), fluoxetine hydrochloride (FLH), and paroxetine hydrochloride (PAH) in vitro against C. gattii. The antifungal activity of SSRI using the microdilution method revealed a minimal inhibitory concentration (MIC) of 31.25 μg/ml. The combination of FLH or PAH with amphotericin B (AmB) was analyzed using the checkerboard assay and the synergistic effect of SSRI in combination with AmB was able to reduce the SSRI or AmB MIC values 4-8-fold. When examining the effect of SSRI on the induced capsules, we observed that FLH and PAH significantly decreased the size of C. gattii capsules. In addition, the effects of FLH and PAH were evaluated in biofilm biomass and viability. The SSRI were able to reduce biofilm biomass and biofilm viability. In conclusion, our results indicate the use of FLH and PAH exhibited in vitro anticryptococcal activity, representing a possible future alternative for the cryptococcosis treatment.